Implementasi Akad Ijarah dalam Meningkatkan Pendapatan Mitra Ojek Online Abang Kurir Bangkalan - Irdlon Sahil; Khoirun Nisa' (Journal of Economic and Islamic Research, 2024)
This research is included in qualitative research using field research methods. The subjects of the study are the owners, employees/drivers, and consumers/business partners of Abang Courier Bangkalan (ABANK). Sampling uses the Snow Ball Sampling technique because it can expand the research subject. The purpose of this study is first, to find out how the implementation of the ijarah contract in online motorcycle taxis Abang Courier Bangkalan (ABANK). Second, to find out whether by joining as a partner of online motorcycle taxis bangkalan can increase income. This research was conducted at the Home Base Abang Courier Bangkalan (ABANK) located at Jl. Letnan Singosastro Gang 3 No 1 Kraton Bangkalan. Data collection techniques use observation, interviews, and documentation, while checking validity using source triangulation, technique triangulation, and time triangulation. So it come to the conclusion. first, the implementation of the ijarah contract at Abang Courier Bangkalan (ABANK) has fulfilled the pillars & conditions of ijarah, namely consumers rent services from Abang Courier Bangkalan (ABANK), and then pay wages/ujrah according to its provisions. Second, based on interview results partners who joined with online motorcycle taxis Abang Courier Bangkalan (ABANK) there are 45 stalls/shops, which are in the Bangkalan area. There are several advantages and disadvantages in joining as a partner of online motorcycle taxis Abang Courier Bangkalan (ABANK), which can facilitate the process of delivering orders and can promote goods online on delivery services and advertisements using social media, both whatsapps or instagram. While the disadvantages are not including a list of fares on ABANK Passenger services, not including a list of shipping costs on social media when ads are published, it become an anomaly in society about how much food is sold. In this case, there is  potential harm to consumers in terms of comfort and satisfaction, but there is no material loss. Because no party is harmed, and both parties are willing and ridho, then the ijarah contract that is carried out is legally valid. Apart from that, some of these shortcomings do not affect sales results, this is proven by the increasing number of partners joining the Abang Courier Bangkalan (ABANK) online motorcycle taxi and the increase in profits from these partners, so that partners are increasingly active in increasing the types of goods sold.